Chaotic Binary Modulation Excitation Sequences for Multichannel Ultrasonic Ranging System - Zhenjing Yao; Jingsong Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A crosstalk elimination method by using the optimal binary excitation sequences modulated with chaotic codes, which includes chaotic binary amplitude shift keying (c-BASK), chaotic binary phase shift keying (c-BPSK) and chaotic binary frequency shift keying (c-BFSK), is proposed in this paper. The selection of the optimal chaotic initial values with the best echo correlation characteristics is realized by adopting a genetic algorithm. A square wave is used as the carrier of the chaotic binary modulation methods in order to reduce hardware cost. However, it could suffer from the decreased energy efficiency caused by mismatching spectrum with ultrasonic ranging system. The parameters of the chaotic binary modulation methods are configured to make their central frequency and bandwidth matched with that of the ultrasonic ranging system very well. Experiments have been conducted using an ultrasonic ranging system that consists of eight-channel SensComp 600 series instrument-grade electrostatic sensors excited with chaotic binary sequences. Experimental results show that the c-BFSK outperforms the c-BASK and c-BPSK in terms of the energy efficiency, e.g., 0.3508  vs. 0.3365  and 0.3279 , respectively. And the optimized c-BFSK sequence also has the best echo correlation characteristics among the chaotic binary modulation sequences. http://dx.doi.org/10.11591/telkomnika.v12i12.4640